HDAC3-mediated silencing of miR-451 decreases chemosensitivity of patients with metastatic castration-resistant prostate cancer by targeting NEDD9. (30th June 2018) - Chen, Dong-qin; Yu, Chen; Zhang, Xue-feng; Liu, Zhong-fang; Wang, Rui; Jiang, Min; Chen, Hao; Yan, Feng; Tao, Min; Chen, Long-bang; Zhu, Hong; Feng, Ji-feng
Background: Treatment of metastatic castration-resistant prostate cancer (mCRPC) with docetaxel often fails due to the emergence of chemoresistance. Thus, restoring chemosensitivity to docetaxel-based therapies remains a challenge in mCRPC treatment. Methods: microRNA (miR)-451 expression was measured in docetaxel-treated prostate cancer cells and tumor tissues by quantitative reverse-transcription polymerase chain reaction . Cell-counting kit 8 assay was performed to determine docetaxel chemoresistance. Neural-precursor-cell-expressed developmentally downregulated protein 9 (NEDD9) was identified as a novel target of miR-451 by dual-luciferase reporter system. Chromatin immunoprecipitation and co-immunoprecipitation assay were performed to confirm that histone deacetylase 3 (HDAC3)/Sp1 (a highly evolutionarily conserved transcription factor) interacted with the Sp1 binding sites in miR-451 promoter. Results: miR-451 was found to be silenced in docetaxel-treated prostate cancer cells and mCRPC tissues. Low miR-451 expression was closely associated with a high Gleason score, high Eastern Cooperative Oncology Group performance status score, visceral metastasis and poor prognosis. Low expression of miR-451 was significantly correlated with short progression-free survival (PFS) and overall survival (OS) according to Kaplan–Meier analysis, and miR-451 was determined to be an independent poor prognostic factor for PFS and OS in mCRPC patients by univariate and multivariate Cox regression analyses. NEDD9 was identified as a new and functional target of miR-451. Restoration of NEDD9 partially reversed the effects of miR-451 on enhancing chemosensitivity of prostate cancer cells. HDAC3 was confirmed to be involved in silencing of miR-451 expression in prostate cancer cells. Conclusions: The current data revealed a new HDAC3/Sp1/miR-451/NEDD9 signaling axis that regulates the chemosensitivity of prostate cancer cells and represents a novel therapeutic target for chemosensitizing mCRPC.